Multichannel engagement and digital marketing at Sanofi: the first mover in pharmaceutical industry in Bangladesh during covid-19 - Shahriar, MD. Sohan (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.